Comparing the global and merged with the local and separate: On a downside to the integration of regions and nations - Oded Stark (University of Tübingen, Faculty of Economics and Social Sciences, 2015)
This paper looks at the integration of regions and nations through the prism of the merger of populations (societies). The paper employs a particular index of social stress. Stylized examples of the merging of two populations suggest that with integration, the social stress index will increase. The examples form the basis for the development of new formulas for calculating the social stress of an integrated population as a function of the levels of social stress of the constituent populations when apart. The formulas reveal that the social stress of an integrated population is higher than the sum of the levels of social stress of the constituent populations when apart. This raises the distinct possibility that the merging of populations may be a social liability: integration may fail to give the populace a sense of improved wellbeing.
urn:nbn:de:bsz:21-dspace-666008
Keywords: D02; D63; F55; P51; 330; Integration of regions and nations; Merging populations; Social welfare